Role of Biofilm-Associated Protein Bap in the Pathogenesis of Bovine Staphylococcus aureus - Cucarella, Carme (American Society for Microbiology, 2004)
Staphylococcus aureus is a common cause of intramammary infections, which frequently become chronic, associated with the ability of the bacteria to produce biofilm. Here, we report a relationship between the ability to produce chronic bovine mastitis and biofilm formation. We have classified bovine mastitis S. aureus isolates into three groups based on the presence of particular genetic elements required for biofilm formation: group 1 (ica(+) bap(+)), group 2 (ica(+), bap negative), and group 3 (ica negative, bap negative). Overall, animals naturally infected with group 1 and 2 isolates had a lower milk somatic cell count than those infected with isolates of group 3. In addition, Bap-positive isolates were significantly more able to colonize and persist in the bovine mammary gland in vivo and were less susceptible to antibiotic treatments when forming biofilms in vitro. Analysis of the structural bap gene revealed the existence of alternate forms of expression of the Bap protein in S. aureus isolates obtained under field conditions throughout the animal's life. The presence of anti-Bap antibodies in serum samples taken from animals with confirmed S. aureus infections indicated the production of Bap during infection. Furthermore, disruption of the ica operon in a bap-positive strain had no effect on in vitro biofilm formation, a finding which strongly suggested that Bap could compensate for the deficiency of the PIA/PNAG product (a biofilm matrix polysaccharide). Altogether, these results demonstrate that, in the bovine intramammary gland, the presence of Bap may facilitate a biofilm formation connected with the persistence of S. aureus.